2018
DOI: 10.3389/fimmu.2018.01051
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Indoleamine 2,3-Dioxygenase Induced by IFN-γ and TNF-α as Potential Biomarker of Prostate Cancer Progression

Abstract: Inflammation has been suggested to play an important role in onset and progression of prostate cancer (PCa). Histological analysis of prostatectomy specimens has revealed focal inflammation in early stage lesions of this malignancy. We addressed the role of inflammatory stimuli in the release of PCa-specific, tumor-derived soluble factors (PCa-TDSFs) already reported to be mediators of PCa morbidity, such as indoleamine 2,3-dioxygenase (IDO) and interleukin (IL)-6. Inflammation-driven production and functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 56 publications
(64 reference statements)
3
53
0
1
Order By: Relevance
“…In addition, IDO1 plays a key role in promoting tumor neovascularization by modulating the expression of interferon-γ (IFN-γ) and interleukin-6 (IL-6) [ 10 , 11 ]. In prostate cancer cells, IFN-γ and TNF-α-treatment induce IDO1 and IL-6 gene expression [ 12 ]. Furthermore, IDO1 is involved in the formation of resistance to immune checkpoint inhibitors [ 13 ], and the combination of an IDO1 inhibitor with checkpoint inhibitors represents an alternative strategy in cancer immunotherapy [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, IDO1 plays a key role in promoting tumor neovascularization by modulating the expression of interferon-γ (IFN-γ) and interleukin-6 (IL-6) [ 10 , 11 ]. In prostate cancer cells, IFN-γ and TNF-α-treatment induce IDO1 and IL-6 gene expression [ 12 ]. Furthermore, IDO1 is involved in the formation of resistance to immune checkpoint inhibitors [ 13 ], and the combination of an IDO1 inhibitor with checkpoint inhibitors represents an alternative strategy in cancer immunotherapy [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The third target is PD-L1, a ligand of PD-1, whose expression is decreased in the inflammatory state (not expressed at basal state). It has been confirmed that IDO inhibitor stimulates tryptophan degradation activity in a dose-dependent manner (12).…”
Section: Discussionmentioning
confidence: 92%
“…IDO gene expression has been detected in human prostate cancers [ 131 ], however, IDO activity is more typically measured by serum kynurenine and tryptophan levels, yielding a (kyn:trp) ratio. This ratio has been debated as a biomarker of prostate cancer detection or progression [ 132 , 133 ]. In recent studies, we assessed serum kyn:trp ratios from patients with different stages of prostate cancer and found that IDO activity increased with stage of disease [ 10 ].…”
Section: Ido Inhibitorsmentioning
confidence: 99%